INVESTIGATION OF MICROBIAL COUNT IN THE SOIL AND EARTHWORM GUT (EUDRILUS EUGENIAE) - V, TAMIZHAZHAGAN; K, PUGAZHENDY; V, SAKTHIDASAN; K, REVATHI; M, BARANITHARAN (Innovare Journal of Agricultural Sciences, 2016)
ABSTRACTÂ The soil microbes are highest in compared with earthworm gut of Â Eudrilus eugeniae. MicrobesÂ are soaring numbers of present in middle gut and several nutrients are gift within the soil. In soil, including Â pH, Â nitrogen, Â phosphorus, Â potassium, Â zinc, Â manganese, Â iron Â and Â copper. Â Earthworm gut from E. eugeniae compared with soil contains highest bacterium and fungi. E. eugeniae gut and soil present in the bacterial colony (Total count Â - 787.33; Per cent â€“ 78.7%); fungal colony (Total Â count Â â€“ Â 610.66; Â Per Â cent Â â€“ Â 61.0 Â %). Â From Â the Â results Â it Â can Â be Â terminated Â the Â bacterial populations was a lot of within the soil and midgut region of E. eugeniae.Â Keywords: Soil, Earthworm gut, Bacteria, Fungi and Eudrilus eugeniaeÂ